Telemedicine as bridge to the offline world for person affected with problematic internet use or internet use disorder and concerned significant others - Laura Bottel; Bert Theodor te Wildt; Matthias Brand; Magdalena Pape; Stephan Herpertz; Jan Dieris-Hirche (Digital Health, 2023)
Introduction Internet use disorder is a disorder of the digital age and presents a growing problem worldwide . It appears that due to structural and personal barriers, many persons affected (PA) and Concerned Significant Others (CSO) do not reach the health care system so far and thus a chronification of the pathology can proceed. Methods A telemedicine counseling service for PA and CSO of PA unwilling to enter treatment with two webcam-based sessions of 60 minutes for each group was created with the aim of reaching out to PA and CSO to provide a low-threshold support and refer the participants to the local health care system. Motivational interviewing for PA and CRAFT (Community Reinforcement and Family Training) for CSO were used as methods. Participants answered questions about their Internet use and sociodemographic data and six months after participation, participants were asked via email if they entered the local health care system. CSO answered the questions for themselves and in a third-party rating for PA unwilling to enter treatment. Results 107 PA (34 years ( SD  = 13.64), 86% male) and 38 CSO (53 years ( SD  = 6.11), 28.9% male) participated in the two telemedicine sessions. After participation, 43.9% of the PA and 42.1% of the CSO reached the health care system. When there was consistency between the location of telemedicine consultation and treatment locally, over 90% of participants arrived (PA: 92.3%, CSO: 100%). Conclusion The results from this study reveal that telemedicine services could be a promising approach to address PA and CSO and build a bridge to the local health care system. Future studies should verify if these results can be replicated in randomized controlled trials.